CD4+ T cell STAT3 phosphorylation precedes acute GVHD, and subsequent Th17 tissue invasion correlates with GVHD severity and therapeutic response. Issue 4 (6th February 2015) - Betts, Brian C.; Sagatys, Elizabeth M.; Veerapathran, Anandharaman; Lloyd, Mark C.; Beato, Francisca; Lawrence, Harshani R.; Yue, Binglin; Kim, Jongphil; Sebti, Said M.; Anasetti, Claudio; Pidala, Joseph
Abstract : CD4 + T cell STAT3 Y705 activation and subsequent Th17 tissue invasion correlates with acute GVHD after allogeneic hematopoietic cell transplantation. Abstract : Th17 cells contribute to severe GVHD in murine bone marrow transplantation. Targeted deletion of the ROR γ t transcription factor or blockade of the JAK2‐STAT3 axis suppresses IL‐17 production and alloreactivity by Th17 cells. Here, we show that pSTAT3 Y705 is increased significantly in CD4 + T cells among human recipients of allogeneic HCT before the onset of Grade II–IV acute GVHD. Examination of target‐organ tissues at the time of GVHD diagnosis indicates that the amount of ROR γ t + Th17 cells is significantly higher in severe GVHD. Greater accumulation of tissue‐resident Th17 cells also correlates with the use of MTX‐ compared with Rapa‐based GVHD prophylaxis, as well as a poor therapeutic response to glucocorticoids. ROR γ t is optimally suppressed by concurrent neutralization of TORC1 with Rapa and inhibition of STAT3 activation with S3I‐201, supporting that mTOR‐ and STAT3‐dependent pathways converge upon ROR γ t gene expression. Rapa‐resistant T cell proliferation can be totally inhibited by STAT3 blockade during initial allosensitization. We conclude that STAT3 signaling and resultant Th17 tissue accumulation are closely associated with acute GVHD onset, severity, and treatment outcome. Future studies are needed to validate the association of STAT3 activity in acute GVHD. Novel GVHD prevention strategies that incorporate dual STAT3 and mTOR inhibition merit investigation.